2020
DOI: 10.1016/j.jiph.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A new parameter in COVID-19 pandemic: initial lactate dehydrogenase (LDH)/Lymphocyte ratio for diagnosis and mortality

Abstract: Background COVID-19 (Coronavirus Disease-2019) is a pandemic disease, infecting more than 26.5 million people. Since there is no specific and effective treatment; early diagnosis and optimal isolation of the patient are of vital importance. Real-time polymerase chain reaction-based (RT-PCR) analyses do not achieve sufficient sensitivity in the diagnosis of the disease. Methods The data from 2217 patients diagnosed as COVID-19 between March 2020 and June 2020 and hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…LDH, lymphocyte, and LWR are inexpensive, easy to get, and automated factors that timely and effectively forecast the prognosis of the patients with different sicknesses [ 13 17 ]. Previous researches suggested that the performance (accuracy/precision) of the combination of LDH and lymphocyte (LDH/lymphocyte) was better than that of LDH and lymphocyte alone [ 5 ]. However, regarding the value of LDH/lymphocyte and L-LWR in the prognosis of patients with IE, it is still blank.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDH, lymphocyte, and LWR are inexpensive, easy to get, and automated factors that timely and effectively forecast the prognosis of the patients with different sicknesses [ 13 17 ]. Previous researches suggested that the performance (accuracy/precision) of the combination of LDH and lymphocyte (LDH/lymphocyte) was better than that of LDH and lymphocyte alone [ 5 ]. However, regarding the value of LDH/lymphocyte and L-LWR in the prognosis of patients with IE, it is still blank.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphocyte percentage (LWR) was an effective prognostic tool for patients with colorectal cancer [ 4 ]. Lactate dehydrogenase/lymphocyte (LDH/lymphocyte) is associated with mortality in COVID-19 patients [ 5 , 6 ]. However, there is no study that assessed the role of LDH/lymphocyte or LDH/LWR (named as L-LWR) in IE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another author pointed LDH as a more effective marker for severe disease when compared to lymphocyte counts and D-dimer [ 31 ], with more sensitivity and specificity. Another author studied the LDH/lymphocyte ratio to evaluate worse COVID-19 outcomes [ 131 ]. According to this study, the ratio can be used to facilitate diagnosis, since PCR has shown a great number of false negatives.…”
Section: Enzyme Dysregulation Consequencesmentioning
confidence: 99%
“…A previous study at our center has shown that the LDH / lymphocyte ratio (LLR) can be used in the early diagnosis of COVID-19 and predicting mortality [ 20 ]. Based on this, we aimed to determine the effect of LLR on the development of MIS-A, early detection of critical patients and mortality in COVID-19 and MIS-A.…”
Section: Introductionmentioning
confidence: 99%